A critical review of 3D printing and digital manufacturing in construction engineering - Ali, Md. Hazrat; Issayev, Gani; Shehab, Essam; Sarfraz, Shoaib (Emerald, 2022)
Purpose In recent years, 3D printing technologies have been widely used in the construction industry. 3D printing in construction is very attractive because of its capability of process automation and the possibility of saving labor, waste materials, construction time and hazardous procedures for humans. Significant researches were conducted to identify the performance of the materials, while some researches focused on the development of novel techniques and methods, such as building information modeling. This paper aims to provide a detailed overview of the state-of-the-art of currently used 3D printing technologies in the construction areas and global acceptance in its applications. Design/methodology/approach The working principle of additive manufacturing in construction engineering (CE) is presented in terms of structural design, materials used and theoretical background of the leading technologies that are used to construct buildings and structures as well as their distinctive features. Findings The trends of 3D printing processes in CE are very promising, as well as the development of novel materials, will gain further momentum. The findings also indicate that the digital twin (DT) in construction technology would bring the industry a step forward toward achieving the goal of Industry 5.0. Originality/value This review highlights the prospects of digital manufacturing and the DT in construction engineering. It also indicates the future research direction of 3D printing in various constriction sectors.
Keywords: additive manufacturing; rapid prototyping; 3D printing; additive construction; concrete printing